Analisis Biaya Produksi Sebagai Penetapan Harga Jual Makanan Resto Ikan Bakar Taria Minang di Bogor - Taufik Hidayat (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
Production costs are one of the keys to the success of the Taria Minang grilled fish restaurant business, as well as a determinant of the cost of products and at the same time to determine the selling price. This has to do with the fact that sales with a good turnover are a reliable source of income. The pricing of food which directly impacts the turnover owned to pay for all expenses incurred in the business. These costs include equipment costs, employee salaries, fixed assets, and raw materials. The method used is descriptive method using a qualitative approach and using research from the calculation of the cost of production by calculating the costs that have been issued. The costs that have been spent should be a reference for returning business capital with the resulting production capacity, so careful consideration is needed. These considerations such as mark up prices, profit margins, Cost of Goods Sold (HPP). Determining the HPP or Food Cost menu is very important to make a profit in a business. Because in addition to setting menu prices, it is also necessary to implement cost control measures to help achieve the desired profit. The results showed that the Minang dance fish grilled restaurant experienced a stable financial condition and could even achieve maximum results.